Pyridostigmine Protects Against Diabetic Cardiomyopathy by Regulating Vagal Activity, Gut Microbiota, and Branched-Chain Amino Acid Catabolism in Diabetic Mice - Yang, Yang; Zhao, Ming; He, Xi; Wu, Qing; Li, Dong-Ling; Zang, Wei-Jin (Frontiers in Pharmacology, 2021)
The disruption of gut microbes is associated with diabetic cardiomyopathy, but the mechanism by which gut microbes affect cardiac damage remains unclear. We explored gut microbes and branched-chain amino acid (BCAA) metabolite catabolism in diabetic cardiomyopathy mice and investigated the cardioprotective effect of pyridostigmine. The experiments were conducted using a model of diabetic cardiomyopathy induced by a high fat diet + streptozotocin in C57BL/6 mice. The results of high-throughput sequencing showed that diabetic cardiomyopathy mice exhibited decreased gut microbial diversity, altered abundance of the diabetes-related microbes, and increased abundance of the BCAA-producing microbes Clostridiales and Lachnospiraceae. In addition, diabetes downregulated tight junction proteins (ZO-1, occludin and claudin-1) and increased intestinal permeability to impair the intestinal barrier. These impairments were accompanied by reduction in vagal activity that manifested as increased acetylcholinesterase levels, decreased acetylcholine levels and heart rate variability, which eventually led to cardiac damage. Pyridostigmine enhanced vagal activity, restored gut microbiota homeostasis, decreased BCAA-producing microbe abundance and improved the intestinal barrier to reduce circulating BCAA levels. Pyridostigmine also upregulated BCAT2 and PP2Cm and downregulated p-BCKDHA/BCKDHA and BCKDK to improve cardiac BCAA catabolism. Moreover, pyridostigmine alleviated abnormal mitochondrial structure; increased ATP production; decreased reactive oxygen species and mitochondria-related apoptosis; and attenuated cardiac dysfunction, hypertrophy and fibrosis in diabetic cardiomyopathy mice. In conclusion, the gut microbiota, BCAA catabolism and vagal activity were impaired in diabetic cardiomyopathy mice but were improved by pyridostigmine. These results provide novel insights for the development of a therapeutic strategy for diabetes-induced cardiac damage that targets gut microbes and BCAA catabolism.